Propuesta de un plan de mantenimiento preventivo basado en la metodología de las 5Q' S para los equipos de carga del área de empaque de la empresa Cemex - Colombia. (2023)
This maintenance proposal is based on the 5Q'S methodology, which was applied to the loading equipment of the packaging area of the Cemex company - Caracolito, Colombia. An initial diagnosis was carried out on the 5 forklifts and 2 skid steer loaders, where it was determined that the main failures of these equipment are damage to the fan, oil leaks through hoses, damage to the tires and rims and a warning of malfunctions in the forklifts. elevators.